33 Improving Mortality with An Integrated Model of Care for Cervical Spine Fracture in Patients Over 75 Years Old. (6th February 2020) - Mahmood, R; Negasan, C; Manzoor, A; Enwere, P; Arnada-Martinez, A; Walters, H; Yeong, K; Lisk, R
Abstract: Introduction: Cervical spine injury is a potentially life threatening trauma. Given the increase in the number of patients presenting to the emergency department (ED) who are elderly and who have fallen and sustained trauma, it has become ever so challenging to manage this cohort of patients. In addition to diagnostic challenges in the elderly population, a robust, integrated care pathway and comprehensive geriatric assessment with involvement of a geriatrician is essential to provide effective care to these patients who require cervical collar after cervical spine injury to prevent morbidity and mortality. Intervention: Data was gathered about the patient's demographics, nature of cervical spine injury, care required from January 2013 till November 2016 (pre intervention) and from November 2016 till October 2017 (post intervention). Current practice was reviewed which showed significant variability in care provision to patients with cervical spine injury including collar care. An integrated care pathway was designed with involvement of multidisciplinary team (MDT) members to standardise the care of this cohort of patients in our hospital. This included early identification of patients with cervical spine injury, co locating all patients, developing nursing expertise for cervical collar care, sitting up early to prevent complications like aspiration, pressure area care, early nutritional support, training staff in post discharge collar care with developing interface with primary care team. Outcome measures in patients over 75 years including length of stay (LOS) inpatient mortality and at 6 and 12 months were recorded respectively. Results: Total: 54 patients, average age: 86.6 years Conclusions: Cervical spine injuries are common in older patients, who are at greater risk of falls and thus sustaining injuries. Early identification and management of these patients in a clinical area with multidisciplinary approach with appropriate expertise is key to reducing LOS and adverse outcome including mortality.